The effect of barium titanate-coated titanium alloy scaffolds on bone regeneration in osteonecrosis of the femoral head models: a comprehensive analysis based on in vitro and in vivo experiments - Chen, Yu; Ou, Yangfei; Xian, Chunxing; Wu, Hao; Pei, Guoqing; Li, Wei; Wang, Ling; Shi, Lei (Frontiers in Bioengineering and Biotechnology, 2025)
Osteonecrosis of the femoral head (ONFH) is a common condition that greatly affects patients’ quality of life, yet current treatments often have limited effectiveness. This study aimed to explore how a porous titanium alloy scaffold coated with barium titanate (BaTiO3) could promote bone regeneration in ONFH. We employed various research methods including cell culture, piezoelectric property measurements, tissue-engineered scaffold fabrication, and in vitro and in vivo biocompatibility assessments. Our results showed that macrophages had better attachment and growth on the BaTiO3-coated porous titanium alloy (PTB) scaffold than on the uncoated porous titanium alloy (PT) scaffold, with no significant differences in apoptosis rates between the two groups. Furthermore, the PTB scaffolds reduced the expression of bone resorption markers, such as Cathepsin K, TRAP, and RANK, under dynamic loading conditions. This finding indicates their potential to inhibit osteoclast differentiation. Moreover, the BaTiO3 coating enhanced the mechanical properties and biocompatibility of the scaffolds, evidenced by significantly higher alkaline phosphatase activity and calcium nodule formation in MC3T3-E1 osteoblasts cultured on PTB scaffolds. These findings underscore the dual role of BaTiO3 in facilitating cellular responses and modulating signaling pathways involved in bone metabolism. Our study highlights the promise of BaTiO3-coated titanium alloy scaffolds as an innovative approach to enhance bone regeneration in ONFH, paving the way for future clinical applications and the development of advanced biomaterials for bone healing.